Exploring the Integration of Information Systems and Security Challenges in Afghanistan’s Current Market - Sayed Zakariya Habib; Mohammad Ali Fahimi; Mir Mohammad Naim Sadat (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
This study aims to investigate the integration of information systems and the associated security challenges within Afghanistan's current market, emphasizing the complex relationship between technological innovation, governance stability, and institutional readiness. Using the Delphi method, the study engaged experts from academia, government, and the private sector to identify key barriers and enablers shaping Afghanistan's digital transformation. Findings reveal that the country's progress in adopting information systems is hindered by fragmented policies, weak cybersecurity awareness, infrastructure limitations, and dependency on donor-funded projects. Despite growing recognition of the importance of digitalization, Afghanistan's institutional fragility continues to impede coordinated implementation and sustainable innovation. Comparative insights with other emerging markets highlight that long-term investment in digital literacy, regulatory coherence, and private sector engagement are critical to overcoming these barriers. The study highlights the importance of adopting a hybrid developmental model that harmonizes local institutional realities with internationally recognized technological standards, fostering adaptability and resilience within Afghanistan's volatile environment. It advances existing understanding by demonstrating how governance reform, human capital enhancement, and cybersecurity integration function as mutually reinforcing components of the nation's digital transformation. Sustainable progress depends on establishing a unified national vision that bridges technology, education, and governance, thereby reinforcing market integrity and institutional stability amid persistent security and economic uncertainty.